2011
DOI: 10.5657/kfas.2011.44.1.085
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Subtidal Marine Plant Community on the East Coast of Korea

Abstract: The species composition and distributions of benthic marine plants on the East Coast of Korea were studied. We examined all species found in the intertidal and subtidal zones at four sites seasonally from August 2006 to May 2009. Of the 148 species identified, 92 were rhodophytes, 39 were phaeophytes, 16 were chlorophytes, and 1 was a seagrass. The most species (125) were found at Jukbyeon, while the fewest (99) were found at Chuksan. Overall, the numbers of species were highest during the spring and lowest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Clear differences were observed in the composition of dominant macroalgal species and vertical distribution when compared with other sites along the Korean peninsula. Communities at Jusamdo in the Yellow Sea are characterized by Desmarestia ligulata at subtidal depths of 5 m and vertically broad distributions of S. thunbergii (Heo et al 2011); Daejin communities in the East Sea are marked by Symphyocladia latiuscula and Phyllospadix japonicus (Shin et al 2011). These differences were probably due to several factors particular to each local region, such as annual mean sea surface temperature, difference in tidal level, latitude, hydrodynamics, topography, or turbidity (Chung et al 1998, Kim et al 1998, Stewart and Carpenter 2003, Kang et al 2011 macroalgal assemblages near the MLW indicates that the macroalgal assemblages changed dramatically with season closer to the MLW, whereas assemblages in the higher intertidal and deeper subtidal zones were more stable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear differences were observed in the composition of dominant macroalgal species and vertical distribution when compared with other sites along the Korean peninsula. Communities at Jusamdo in the Yellow Sea are characterized by Desmarestia ligulata at subtidal depths of 5 m and vertically broad distributions of S. thunbergii (Heo et al 2011); Daejin communities in the East Sea are marked by Symphyocladia latiuscula and Phyllospadix japonicus (Shin et al 2011). These differences were probably due to several factors particular to each local region, such as annual mean sea surface temperature, difference in tidal level, latitude, hydrodynamics, topography, or turbidity (Chung et al 1998, Kim et al 1998, Stewart and Carpenter 2003, Kang et al 2011 macroalgal assemblages near the MLW indicates that the macroalgal assemblages changed dramatically with season closer to the MLW, whereas assemblages in the higher intertidal and deeper subtidal zones were more stable.…”
Section: Resultsmentioning
confidence: 99%
“…Although numerous studies have described these general zonation patterns, recent studies have suggested that these patterns may not be generalizable across geographic regions because peaks in abundance or diversity are not found consistently in particular depth strata (Balata and Piazzi 2008, Konar et al 2009, Heo et al 2011, Kang et al 2011. Therefore, there is great interest in investigating not only these exceptional patterns but also different zonation patterns in species composition, diversity, abundance, and community dynamics among areas at local scales (Konar et al 2009, Heo et al 2011, Kang et al 2011, Shin et al 2011.Macroalgal growth is influenced by multi-factorial in- This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. …”
mentioning
confidence: 99%
“…이를테면 Kim and Lee (1981)는 경북 월성군 일대 조간대의 해조군집을 대상으로 배열법 (ordination)과 무리분석 (cluster analysis)을 수행하여 조간대 내의 조위별 차이보다는 지리적 인 차이, 특히 외해로의 파도의 노출 정도의 차이에서 유의적 인 변이가 나타남을 관찰하였다. 이후 동해안 전역에 걸친 해조군집의 연구는 Lee et al (2001), Choi et al (2006), Shin et al (2008a2011) 등에서 상세하게 다루고 있다.…”
Section: 서 론unclassified